(Invited) Tensile Strain Engineering and Defects Management in GeSn Laser Cavities. (8th September 2020) - EL Kurdi, Moustafa; Elbaz, Anas; Wang, Binbin; Sakat, Emilie; Herth, Etienne; Patriarche, Gilles; Pantzas, Konstantinos; Sagnes, Isabelle; Sauvage, Sebastien; Checoury, Xavier; Chelnokov, Alexei; Reboud, Vincent; et al.
Abstract : Recent achievements of direct band gap with germanium by alloying with tin or by tensile strain engineering has enabled multiple times demonstration of laser emission in the 2-4µm wavelength range. This fast and promising emergence of CMOS-compatible laser technology in the Mid-IR faces, however, major issues, e.g., high power density of thresholds, hindering the aim to be integrated on a silicon chip and develop low cost sensing and/or Datacom devices. In this report we show that combining both tensile strain and Sn alloying can effective engineer the material band structure and its optical gain properties. We also evidence the importance of defects management on GeSn lasing characteristics, beyond the band structure engineering. We discuss the potential of GeSnOI technology to address above aspects, which enabled to drastically reduce the lasing thresholds in microdisk laser cavities and reach continuous-wave operation in GeSn active media.